The Dimensions of Occupation in Kurdish and Persian Poetry A Collection of Typical Poetry - Mohammed Noori Amin, Mohammed Amin (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
This research is a study of the comparison between Kurdish and Persian literature in a sensitive historical era, when the Persian Iranian state was occupied by the Russians in the north and the English to the south, while Kurdistan was occupied by Turks after the demise of the Emirate Al-Bab And then the English occupation replaced the Turks and Kurdistan became under the yoke of british colonialism directly, and the front of the Poets of the Kurds and Persians occupation with their national poems to fuel the fire of resistance and flame to the masses with their enthusiastic slogans in order to get rid of the greedy and wanton occupiers. But there is a radical difference in the contents of the poets of the Kurdish poets and the national persians and resistance to colonialism، if we examine the contents of Kurdish poetry in this era to show us clearly, that Kurdish poetry has a human and liberal content that seeks to rid the country of colonialism and its scourges without compromising the rights of Others do not frown and do not slander towards minority rights. But they call for cohesion and solidarity for all in order to reach the desired goal، which is to rid and liberate the homeland. i. e. in other words، the knowledge of Kurdish poets is not racist or chauvinism.. in the most accurate words, the reunification under the roof of the homeland Humanity is the goal of their manchudonbel. While persian poets sang in the dreamy past when they were one of the 8 powerful empires that prayed and toured the parts of the globe that were under their rule, when they were usurped and occupied. Not to mention their narrow minds in the line of others, this is what we see in their poetic texts, that all they think about in their poems and boast without shame and revered is to try to wipe and suck the non-Persian identity of Arabs, Kurds and blog...... And other Iranian nations and peoples, the knowledge and culture of iranian poets as a whole stem from the thinking inherited from the ancestors and glorify what Firdousi, the spiritual father of the Persian chauvinist mentality, said in his epic known as magnanimity.